Optimizing the SPAM Network in Huta Padang Village: A Regional Planning Approach to Improve Access to Clean Water - Ahmed Ridho Siagian; Abdi Sugiarto (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to examine the Optimization of SPAM Network in Huta Padang Village: A Regional Planning Approach to Improve Access to Clean Water. The qualitative research methods applied in this study allow for an in-depth understanding of the optimization of SPAM networks in Huta Padang Village by considering the perspective of the community and local conditions. Data collection techniques such as in-depth interviews, field observations, and document studies, as well as systematic analysis, provide comprehensive insights into the needs and opportunities to improve access to clean water. The results of the research The regional planning approach is proven to provide a systematic and structured way to overcome existing challenges. Identify additional water resources that can be used sustainably to increase water supply. Renewing damaged pipelines, installing pumping systems in hilly areas, and conducting integrated distribution to improve the pressure and quality of water flow. Implementing zoning to manage water pressure and allocation according to the needs of each area, so that water supply is more even and efficient. Optimizing the SPAM network in Huta Padang Village through a regional planning approach can significantly increase access to clean water. Through solutions that focus on infrastructure management, community participation, and the use of technology, access to clean water for all village communities can be more guaranteed. These steps are expected to create a healthier environment and support the welfare of the people of Huta Padang Village in a sustainable manner.